Investigation of CVD graphene topography and surface electrical properties. (29th February 2016) - Wang, Rui; Pearce, Ruth; Gallop, John; Patel, Trupti; Zhao, Fang; Pollard, Andrew; Klein, Norbert; Jackman, Richard; Zurutuza, Amaia; Hao, Ling
Abstract: Combining scanning probe microscopy techniques to characterize samples of graphene, a selfsupporting, single atomic layer hexagonal lattice of carbon atoms, provides far more information than a single technique can. Here we focus on graphene grown by chemical vapour deposition (CVD), grown by passing carbon containing gas over heated copper, which catalyses single atomic layer growth of graphene on its surface. To be useful for applications the graphene must be transferred onto other substrates. Following transfer it is important to characterize the CVD graphene. We combine atomic force microscopy (AFM) and scanning Kelvin probe microscopy (SKPM) to reveal several properties of the transferred film. AFM alone provides topographic information, showing 'wrinkles' where the transfer provided incomplete substrate attachment. SKPM measures the surface potential indicating regions with different electronic properties for example graphene layer number. By combining AFM and SKPM local defects and impurities can also be observed. Finally, Raman spectroscopy can confirm the structural properties of the graphene films, such as the number of layers and level of disorder, by observing the peaks present. We report example data on a number of CVD samples from different sources.